2020
DOI: 10.3389/fmech.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Transient and Steady Sliding Friction of Elastomers: Impact of Vertical Lift

Abstract: The sliding friction of elastomers has been investigated numerically and theoretically for the line contact between a cylindrical rigid indenter and a "frictionless" Kelvin-Voigt foundation. The onset of sliding under an abrupt increase in the drive velocity has been simulated with different boundary conditions of the rigid indenter. When the rigid indenter is not allowed to move in any direction, just an abrupt change in the friction force appears, which is not accompanied by any transient processes. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Hence, an optimized layered structure can be employed to achieve superlubricity in the PMMA-CPB. One possible mechanism is that a decrease in the CPB thickness due to the mild wear increases the contact stiffness, causing a reduction of the indentation depth, which decreases the friction force due to the CPB viscoelasticity. , Further studies are necessary to elucidate the details of the relationship between superlubricity and the layered structure of PMMA-CPBs.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, an optimized layered structure can be employed to achieve superlubricity in the PMMA-CPB. One possible mechanism is that a decrease in the CPB thickness due to the mild wear increases the contact stiffness, causing a reduction of the indentation depth, which decreases the friction force due to the CPB viscoelasticity. , Further studies are necessary to elucidate the details of the relationship between superlubricity and the layered structure of PMMA-CPBs.…”
Section: Resultsmentioning
confidence: 99%
“…( 9) with Eq. ( 1), we can determine the horizontal one f x (x) geometrically: (10) where we used that the local contact force subject to the probe is perpendicular to the probe surface slope at the local contact point [26]. Then, using f z (x) and f x (x) provides the contact load W, the friction force F, and the friction coefficient μ from Eqs.…”
Section: Local Contact Forcementioning
confidence: 99%
“…One of the noteworthy characteristics of viscoelastic friction is its velocity dependence, exhibiting a bell shape in the semi-logarithmic plot of the friction Toshiki Watanabe and Ken Nakano * coefficient against the velocity, as obtained by famous Grosch's experiments [5]. Although the above theories [17][18][19][20][22][23][24][25][26][27] can explain the bell-shaped velocity-dependent friction coefficient, two origins seem hidden.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an experimental investigation 14 , a master curve of µ based on the Williams-Landel-Ferry theory 15 showed that the viscoelastic properties of rubber could determine µ. The relationship between friction behavior and viscoelastic properties has been theoretically investigated based on a combined series of Kelvin elements 16,17 . Furthermore, the strain distribution during rubber friction has been investigated using the nite element method (FEM) 18-23 .…”
Section: Introductionmentioning
confidence: 99%